2017
DOI: 10.21276/apalm.1154
|View full text |Cite
|
Sign up to set email alerts
|

A Cytohistopathological Correlation of Thyroid Lesions with Critical Evaluation Of Discordant Cases: An Experience At A Tertiary Care Hospital

Abstract: Background: Fine Needle Aspiration Cytology (FNAC) is important for pre-operative diagnosis of benign and malignant thyroid lesions. It is usually the first line of investigation and a minimally invasive diagnostic procedure whose essential role is to diagnose and distinguish benign from malignant lesions. Thus the present study was undertaken to determine sensitivity, specificity and accuracy of FNAC in the diagnosis of thyroid lesions and to correlate cytological findings with histopathology. Methods:A prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…In our study, on histopathology, benign thyroid lesions were more common at 91.3% and malignant lesions were 8.6% which is comparable with the findings of Kantasueb et al 16 [9] 2015 96.3% 100% 96.6% Pandey et al [17] 2012 57.1% 90% 80.2% Gupta et al [18] 2010 80% 86% 84% Hathila et al [11] 2016…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, on histopathology, benign thyroid lesions were more common at 91.3% and malignant lesions were 8.6% which is comparable with the findings of Kantasueb et al 16 [9] 2015 96.3% 100% 96.6% Pandey et al [17] 2012 57.1% 90% 80.2% Gupta et al [18] 2010 80% 86% 84% Hathila et al [11] 2016…”
Section: Discussionsupporting
confidence: 89%
“…Aramani et al 9 studied 60 patients with thyroid lesions and observed the age range from 15 to 65years with predominance of female patients. The male to female ratio was 1:14.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were others who have just mentioned “blood only/lack of cellularity/poor quality smears/presence of obscuring factors” as the reason for calling a sample unsatisfactory [ 15 , 22 , 24 ]. Still, some studies have not specified the criteria used for adequacy [ 27 , 28 , 57 ].…”
Section: Non-diagnostic Criteria For Cytological Diagnosismentioning
confidence: 99%
“…Cystic change and/or hemorrhage in neoplasms is seen in up to 25% of papillary carcinomas, 20% of follicular neoplasms and in 26% of follicular carcinomas. 6 This is due to typical appearances of follicular cells with moderate variation in size. Such a change can be observed in benign lesions also as hyperplastic reaction of thyroid cells.…”
Section: Amrikachi Et Al (2001)mentioning
confidence: 99%
“…3 Despite the improvement in the diagnosis of thyroid lesions using ultrasonography and radio nucleotide scanning, fine needle aspiration cytology (FNAC) has emerged as the first step in the diagnostic management of thyroid nodules. 4,5 It has proven to be a cost-effective tool 6,7 in the selection of patients requiring surgical intervention, halving the number of patients undergoing thyroid surgery and doubling the incidence of malignancy in the resected specimens 4. However, interpretive or sampling errors account for false diagnoses in FNAC. 2 Hashimoto's thyroiditis is the most common cause of false-positive cytology for malignancy.…”
Section: Introductionmentioning
confidence: 99%